Exploring the antibacterial and dermatitis-mitigating properties of chicken egg white-synthesized zinc oxide nano whiskers - Abdikakharovich, Sidikov Akmal; Rauf, Mohd A.; Khattak, Saadullah; Shah, Junaid Ali; Al-Keridis, Lamya Ahmed; Alshammari, Nawaf; Saeed, Mohd; Igorevich, Sadykov Aslan (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Zinc oxide nanoparticles (ZnO-NPs) have garnered considerable interest in biomedical research primarily owing to their prospective therapeutic implications in combatting pathogenic diseases and microbial infections. The primary objective of this study was to examine the biosynthesis of zinc oxide nanowhiskers (ZnO-NWs) using chicken egg white (albumin) as a bio-template. Furthermore, this study aimed to explore the potential biomedical applications of ZnO NWs in the context of infectious diseases. Methods The NWs synthesized through biological processes were observed using electron microscopy, which allowed for detailed examination of their characteristics. The results of these investigations indicated that the NWs exhibited a size distribution ranging from approximately 10 to 100 nm. Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) mapping analyses successfully corroborated the size, dimensions, and presence of biological constituents during their formation. In this study, XTT assay and confocal imaging were employed to provide evidence of the efficacy of ZnO-NWs in the eradication of bacterial biofilms. The target bacterial strains were Staphylococcus aureus and Escherichia coli. Furthermore, we sought to address pertinent concerns regarding the biocompatibility of the ZnO-NWs. This was achieved through comprehensive evaluation of the absence of cytotoxicity in normal HEK-293T and erythrocytes. Results The findings of this investigation unequivocally confirmed the biocompatibility of the ZnO-NWs. The biosynthesized ZnO-NWs demonstrated a noteworthy capacity to mitigate the dermatitis-induced consequences induced by Staphylococcus aureus in murine models after a therapeutic intervention lasting for one week. Discussion This study presents a comprehensive examination of the biosynthesis of zinc oxide nanowhiskers (ZnO-NWs) derived from chicken egg whites. These findings highlight the considerable potential of biosynthesized ZnO-NWs as a viable option for the development of therapeutic agents targeting infectious diseases. The antibacterial efficacy of ZnO-NWs against both susceptible and antibiotic-resistant bacterial strains, as well as their ability to eradicate biofilms, suggests their promising role in combating infectious diseases. Furthermore, the confirmed biocompatibility of ZnO-NWs opens avenues for their safe use in biomedical applications. Overall, this research underscores the therapeutic promise of ZnO-NWs and their potential significance in future biomedical advancements.